La Revue du Practicien; Urgences respiratoires de l adulte (2003)
Openings Medical heuristics Causality and statistical association (2) Mechanical determinism and stochastic model From doctor`s memory Respiratory emergencies in adults Foreword Severe acute asthema Acute respiratory distress syndrome Cardiogenic pulmonary edema in the elderly Pneumothorax Thoracic trauma Haemoptysis Non-invasive ventilation Acute laryngeal dyspnea For practice Academic references Medical prescription: press review Type I diabetes mellitus in children and adults Sexually transmitted diseases. Gonococcal disease, Chlamydia, syphilis Andropause Estra-uterine pregnancy Diplopia. Diagnostic orientation Assessment of the severity and search for early complications in a traumatic brain injury